Hybrid efficient compression method for electrocardiogram signal transmission based on discrete wavelet transform and principal component analysis - Abdulbaqi, Azmi Shawkat (Tanjong Malim, 2020)
Hybrid efficient compression method for electrocardiogram signal transmission based on discrete wavelet transform and principal component analysis by Abdulbaqi, Azmi Shawkat